2022
DOI: 10.1038/s41746-022-00676-9
|View full text |Cite
|
Sign up to set email alerts
|

Wearable accelerometer-derived physical activity and incident disease

Abstract: Physical activity is regarded as favorable to health but effects across the spectrum of human disease are poorly quantified. In contrast to self-reported measures, wearable accelerometers can provide more precise and reproducible activity quantification. Using wrist-worn accelerometry data from the UK Biobank prospective cohort study, we test associations between moderate-to-vigorous physical activity (MVPA) – both total MVPA minutes and whether MVPA is above a guideline-based threshold of ≥150 min/week—and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Third, given that varying activity patterns may affect muscle condition, we assessed associations between PA patterns and prevalence of muscle pain or soreness in the past 3 days in a subsample since it was only collected in the 2011–2012 and 2013–2014 cycles. Fourth, we assessed alternative definitions of the WW pattern and RA pattern [24]. WW was total PA at or above 150 min/week and ≥50% of total PA over one or two sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Third, given that varying activity patterns may affect muscle condition, we assessed associations between PA patterns and prevalence of muscle pain or soreness in the past 3 days in a subsample since it was only collected in the 2011–2012 and 2013–2014 cycles. Fourth, we assessed alternative definitions of the WW pattern and RA pattern [24]. WW was total PA at or above 150 min/week and ≥50% of total PA over one or two sessions.…”
Section: Methodsmentioning
confidence: 99%
“…They found that compared to those who were inactive, participants who were insufficiently active, regularly active or "weekend warriors" all had a more favorable vascular health, with no difference between the regularly active or the "weekend warriors." When looking at downstream cardiovascular events in the UK Biobank study, Kurshid et al 7 similarly found that those who completed ≥150 min/week through being "active regularly" or "weekend warriors" both had lower risk of cardiovascular events compared to those who were inactive. 7 However, grouping people based on combinations of duration, intensity and frequency of PA makes it difficult to isolate the effect of PA pattern from overall PA volume, of which we know is beneficially associated with vascular health.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been associated with lower risk of a wide range of non-communicable diseases and is a key feature of public health guidelines for cardiovascular health [1][2][3] . While researchers most commonly report device-measured activity in terms of overall acceleration or time-use behaviours derived from intensity thresholds 4 , the reporting of steps is a more intuitive measure of physical activity intrinsically linked to the key biomechanical feature of human gait 5 .…”
Section: Introductionmentioning
confidence: 99%